Role of technology attraction and parasocial interaction in social shopping websites. (April 2020) - Zheng, Xiabing; Men, Jinqi; Xiang, Li; Yang, Feng
Highlights: Parasocial interaction has a significant effect on social commerce intention. Social attraction and task attraction directly influence users' parasocial interaction. Physical attraction indirectly influences users' parasocial interaction. This study is based on the context of social shopping websites. Abstract: Attraction is an essential factor in interactions between individuals. Some existing studies have examined multiple dimensions of attraction including social, physical, and task attraction. However, the mechanism behind these three attraction dimensions and parasocial interaction in social shopping websites has not been well examined. This study adopts technology attraction theory and parasocial interaction theory to analyze how three types of technology attraction affect parasocial interaction, which consequently influences users' social commerce intention. This study conducted a survey to analyze the proposed empirical model and analyzed data from 248 social shopping website users. The results indicate that social attraction and task attraction positively and directly affect the users' parasocial interaction. In contrast, physical attraction indirectly influences users' parasocial interaction via social attraction and task attraction, respectively. Parasocial interaction consequently influences users' social commerce intention. Discussion, limitations, and implications of the study are presented.